Metopina Macquart (Diptera: Phoridae) of Israel, with description of a new species, new records and an identification key - Mostovski, Mike B. (Zootaxa, 2016)
Metopina kuslitzkyi sp. n. with a rudimentary anterior flap on tergite 5 in female is described from Israel. Four other species, the Palaearctic Metopina braueri, M. pileata, M. ulrichi and Afrotropical M. obsoleta, have been recorded from Israel for the first time, in addition to the previously known M. heselhausi. An illustrated identification key to the Israeli species of Metopina is provided.